(untitled) (In situ, 2024)
Observations are made about the cultural property, the ruins of a small church of unknown dedication at the location of Musapstan in Crno near Zadar. In 2023, the Department of Archaeology of the University of Zadar conducted archaeological trial excavation of the church and neighboring land plots due to the planned construction of a residential building.